USE OF ARTIFICIAL INTELLIGENCE IN STUDENT TRAINING IN MUSIC EDUCATION - Nodirbek Tolkunovich Makharov; Sitora Sunnatqizi Ibragimova; Akmal Umaro‘g‘li Safarov; Nozimaxon Maxmurjonqizi Mirzajonova; Dilrabo Abduvaliyevna Abdurashidova (The Bioscan, 2024)
This article analyzes the effectiveness of using artificial intelligence technologies in student training in the field of music education. Artificial intelligence (AI) is widely used to improve modern pedagogical methods, develop students' creative abilities, and make the teaching process more interactive. The article examines how AI systems can be used in music education, in particular, in creating musical works, analyzing music, and providing individual support to students. The role of AI technologies in the integration of music teaching, in creating and analyzing musical works, as well as in creating educational resources tailored to the individual needs of students, is analyzed. The possibilities of AI in developing interactive and flexible teaching methods, and its role in improving the process of effective communication and knowledge exchange between teachers and students are discussed. The article also highlights the positive and negative aspects of AI technologies in music education, including automated and personalized aspects of the learning process. The article concludes with analytical thoughts on the future of using artificial intelligence in music education and how it can change the pedagogical process. The possibilities and limitations of using artificial intelligence in the educational process are discussed, as well as new educational resources created for teachers and students. As a result, the impact of AI technologies on music education and future prospects in this area are shown.